The Importance of Adapting And Updating The New Supply Chain Capabilities For Sustainability In The Business of Supply Equipment In Oil and Gas Industrial Projects - Samsul Rizal (UniSadhuGuna Business School, 2023)
The supply of equipment in oil and gas industrial projects requires high standards and specifications due to high requirements of safety and reliability. Delay of equipment delivery is very sensitive as the impact will be direct to the whole project, while the delay of project completion will disrupt PSC’s (Partnership Status Contractor’s) initial production. Ultimately, this would disrupt the oil and gas production target of the Government of Indonesia. Operational data show that a lot of delay is caused by the ineffectiveness of supply chain management at PT AMN. These conditions increased complaints and penalties from customers while at the same time decreasing the operational efficiency of PT AMN. To overcome this problem and enhance customer satisfaction it is required to evaluate the existing supply chain capabilities and then adapt, update, and develop new supply chain capabilities. Determine new supply chain capabilities of PT AMN, requires analysis data of PT AMN related to customers' needs, internal assessment, existing supply chain, check-list supply chain capabilities, SWOT analysis, five pillars, the landscape of supply chain technology, game changer and risk management analysis for business sustainability. In terms of determining supply chain capabilities, PT AMN is categorized as an Adaptive Initiative or Continuous Improvement Initiative